Bio‐functional hydrogel with antibacterial and anti‐inflammatory dual properties to combat with burn wound infection. Issue 1 (5th July 2022) - Xiong, Yahui; Xu, Yingbin; Zhou, Fei; Hu, Yanke; Zhao, Jingling; Liu, Zhonghua; Zhai, Qiyi; Qi, Shaohai; Zhang, Zhaoqiang; Chen, Lei
Abstract: Burn infection delays wound healing and increases the burn patient mortality. Consequently, a new dressing with antibacterial and anti‐inflammatory dual properties is urgently required for wound healing. In this study, we propose a combination of methacrylate gelatin (GelMA) hydrogel system with silver nanoparticles embed in γ‐cyclodextrin metal–organic frameworks (Ag@MOF) and hyaluronic acid‐epigallocatechin gallate (HA‐E) for the burn wound infection treatment. Ag@MOF is used as an antibacterial agent and epigallocatechin gallate (EGCG) has exhibited biological properties of anti‐inflammation and antibacterial. The GelMA/HA‐E/Ag@MOF hydrogel enjoys suitable physical properties and sustained release of Ag + . Meanwhile, the hydrogel has excellent biocompatibility and could promote macrophage polarization from M1 to M2. In vivo wound healing evaluations further demonstrate that the GelMA/HA‐E/Ag@MOF hydrogel reduces the number of the bacterium efficiently, accelerates wound healing, promotes early angiogenesis, and regulates immune reaction. A further evaluation indicates that the noncanonical Wnt signal pathway is significantly activated in the GelMA/HA‐E/Ag@MOF hydrogel treated group. In conclusion, the GelMA/HA‐E/Ag@MOF hydrogel could serve as a promising multifunctional dressing for the burn wound healing.